Psychophysiological Patterns Related to Success in a Special Operation Selection Course - Hormeño-Holgado, Alberto J.; Nikolaidis, Pantelis T.; Clemente-Suárez, Vicente J. (Frontiers in Physiology, 2019)
Actual theatres of operations require actions from special operations units to be carried out promptly and briefly with high level of readiness and survival. Mission accomplishment depend on their psychological and physiological performance. The aim of the present study was to analyse: (i) the physical parameters related with success in a special operation selection course; and (ii) the modifications of psychological profile of recruits before and after a special operation selection course. Fifty-five soldiers of the Spanish Army (25.1±5.0 years, 1.8±0.1 cm, 76.8±7.9 kg, 24.4±2.5 kg/m2) undertaking a ten weeks special operation selection course performed a series of physiological and psychological tests. Horizontal jump was longer, 50 m sprint was faster and heart rate in the 2000 m test was higher in successful than in non-successful soldiers. The psychological values of life engagement test (LET), acceptance and action questionnaire (AAQ-II), coping flexibility scale (CFS) and perceived stress scale (PSS) did not present significant differences during the entire selection course. A successful special operation selection course was related with higher anaerobic and cardiovascular fitness. This special operation selection course did not modify psychological profile of successful soldiers.